In vitro virucidal activity of povidone iodine gargle and mouthwash against SARS-CoV-2: implications for dental practice - Pouya Hassandarvish; Vunjia Tiong; Nurul Azmawati Mohamed; Harsha Arumugam; Abhishek Ananthanarayanan; Murtaza Qasuri; Yacine Hadjiat; Sazaly Abubakar (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication